Flood Model of Downstream Kali Lahar Using HECRAS - Harifa, Ayisya Cindy; Purnomo, Fadjar; Sutikno, Sutikno (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2023)
Flooding that occurs in the area around Kali Lahar is a problem that always occurs when the rainy season. This research aims to find the causes of flooding in Kali Lahar, located on Jalan Letjen Sutoyo, Malang City, by considering the hydrological conditions in the Kali Lahar subwatershed. The data used in the analysis is rain data from the Sukun, Ciliwung, and Petungsewu stations, with the same data range between 2008 and 2020. There is also spatial data such as DEMNAS and river networks. The analysis is carried out by modeling floods with synthetic unit hydrographs, which are then modeled with HEC-RAS 1D and 2D software to determine whether the river can accommodate flood discharge with a return period of 10 years. The discharge produced by Unit Hydrograph Nakayasu was 134.25 m3/s. This discharge is modeled using HECRAS and produces water levels up to 1.5 m above the banks. Increasing the depth of the channel is an alternative solution for flooding in this area. The simulation results of the new dimension show no flooding in the area around the channel. The results of this research can contribute to the planning and arrangement of existing canals in Malang City so that they can prevent or reduce flooding that occurs.